2016
DOI: 10.1093/heapro/daw087
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health literacy in university students in Vientiane, Lao PDR

Abstract: Health literacy includes the knowledge, motivation and competence of a person to make judgments and decisions on health information in order to promote and maintain their health in relation to health care, disease prevention and health promotion. The role health literacy plays in determining health outcomes makes it an important focus of public health research. In line with a larger Asia wide initiative (HLS-Asia), this study set out to measure health literacy in the Lao People's Democratic Republic (Lao-PDR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In Asia, the level of health literacy among 224 students from two faculties (Science and Health Sciences) was measured. Study findings indicated that 93% of the students had insufficient health literacy [4]. Another study carried out in Turkey, among Nursing students, concluded that 29.3% of the students had an insufficient level of health literacy [5].…”
Section: Health Literacy Levelsmentioning
confidence: 86%
“…In Asia, the level of health literacy among 224 students from two faculties (Science and Health Sciences) was measured. Study findings indicated that 93% of the students had insufficient health literacy [4]. Another study carried out in Turkey, among Nursing students, concluded that 29.3% of the students had an insufficient level of health literacy [5].…”
Section: Health Literacy Levelsmentioning
confidence: 86%
“…With the cutoff value used in previous literature [17], a HL index of 0 to 25 may indicate "inadequate" perceived health literacy, and a value from 26 to 33 was defined as "problematic"; while an HL index in the range of 34 to 42 indicated "sufficient", and a value above 42 may suggest "excellent" perceived health literacy. The same cutoff value was also applied to different domains of information processing [19].…”
Section: Methodsmentioning
confidence: 99%
“…These are healthcare, disease prevention and health promotion. 1 The quality of health services and healthcare providers may be affected by health literacy levels of individuals. 2 Most of the individuals have difficulty in navigating healthcare options and are unable to understand the information provided by health care professionals regardless of their education and social status.…”
Section: Introductionmentioning
confidence: 99%